STRATEGI PENGEMBANGAN KAWASAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN MERAUKE - Sultan; Mujiati; Rante , Harmonis (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2025)
Merauke Regency has vast and strategic agricultural land potential as a national food basket, but ecological, social, and infrastructure challenges remain obstacles to the development of sustainable farm areas. This study aims to formulate a strategy for developing a sustainable food-based agricultural area that is adaptive to local conditions in Merauke. The method used is a qualitative-descriptive approach through literature review and analysis of strategies based on regional potential. The study findings indicate that strategies encompassing optimal land use, technology application, wise natural resource management, infrastructure strengthening, community empowerment, and green economy-based policies can drive the transformation of Merauke's agriculture into a productive, efficient, and sustainable system. Implementation recommendations include a multi-stakeholder collaborative approach, regulatory support, and risk mapping based on spatial data.